1976
DOI: 10.1159/000240803
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Body Size, Thermal Balance and Thermal Insulation of Term Infants under Various Ambient Conditions

Abstract: A gradient layer direct calorimetric study was made on the thermal balance of small-for-date, appropriate-for-date and large-for-date term newborn infants during the first 2 days of life. At ambient temperatures of 28 and 32 °C, the dry and total heat losses per kilogramme body weight were inversely related to body weight. There was a negative correlation between metabolic rate per kilogramme and body weight, whereas in terms of surface area the correlation became positive. A similar tendency without statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Generally speaking, the larger the curvature is, the greater the heat loss is, that is, the surfaceto-mass ratio affects the heat loss as pointed out by Sulyok et al [18]. The present study also showed that the dry heat loss from the infant 59.02 W/m 2 was greater than that from the adult manikin 37.21, conversely the dry heat resistance of the infant clothing 0.049 was less than the adults 0.090.…”
Section: Discussionmentioning
confidence: 98%
“…Generally speaking, the larger the curvature is, the greater the heat loss is, that is, the surfaceto-mass ratio affects the heat loss as pointed out by Sulyok et al [18]. The present study also showed that the dry heat loss from the infant 59.02 W/m 2 was greater than that from the adult manikin 37.21, conversely the dry heat resistance of the infant clothing 0.049 was less than the adults 0.090.…”
Section: Discussionmentioning
confidence: 98%
“…In the early stage, physiological experiments were carried out to monitor their thermo-physiological responses, such as skin temperature, core temperature, and metabolic production. 5,6 Since the experiments on infants had the potential risks of thermal or cold stress, thermal manikins in the shape of an infant have been constructed to estimate the heat loss of a real infant. [7][8][9] Recently, computational fluid dynamics (CFD) techniques have become an essential tool in predicting thermal comfort, with the ability to economically and quickly characterize the temperature and velocity fields and heat transfer coefficient without experimental measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been adopted to evaluate infants' thermal comfort in various environments. In the early stage, physiological experiments were carried out to monitor their thermo‐physiological responses, such as skin temperature, core temperature, and metabolic production 5,6 . Since the experiments on infants had the potential risks of thermal or cold stress, thermal manikins in the shape of an infant have been constructed to estimate the heat loss of a real infant 7–9 .…”
Section: Introductionmentioning
confidence: 99%